Method for modifying polymer barrier films
Patent Information
- Application Number
- JP2021561861
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2019-04-16
- Filing Date
- 2020-04-15
- Publication Date
- 2025-03-04
- Estimated Expiration
- 2040-04-15
Smart Images

Figure 0007638897000001
Abstract
Description
[Technical field]
[0001] The present invention relates generally to barrier films, and in particular to methods of making crosslinked films, including compositions that form such films, and articles of manufacture made with such films. [Background technology]
[0002] Film-based barrier coatings are widely used in packaging materials to prevent the passage of liquids, gases, odorants, etc., including preventing contact between the contents of the package and the permeants. Improving barrier properties is an important goal for manufacturers of films sold to encapsulate products such as food, cosmetics, pesticides, and pharmaceuticals. The use of plastic materials is typically part of such coatings, but in recent years, the use of plastics, especially fossil fuel-based plastics, has fallen out of favor due to consumer / market pressures due to their lasting impact on the environment.
[0003] Oriented films of thermoplastic resins, such as polypropylene, polyester, and polyamide, generally have excellent mechanical properties, heat resistance, and transparency and are widely used as packaging materials. Typical barrier materials are polymer monolayers, bilayer polymer films by coextrusion or lamination, coated monolayers, or bilayer or multilayer films with one or more coatings on one or both surfaces. Other barrier technologies include metallization with thin coatings of aluminum using vacuum deposition onto various base film structures.
[0004] Polyvinyl alcohol (hereinafter sometimes abbreviated as "PvOH") is known as a water-soluble synthetic polymer. PvOH has particularly excellent strength and film-forming properties compared to other synthetic polymers. Therefore, PvOH is used as a material for films and fibers, an additive for paper and fiber processing, an adhesive, a stabilizer for emulsion polymerization and suspension polymerization, a binder for inorganic materials, etc. Thus, PvOH is frequently used in various applications.
[0005] There are many processes for film formation, including aqueous coating and / or dosing, calendaring, extrusion, plastisol casting systems, and organosol casting systems. Extrusion and calendaring are processes that melt the polymer and mold the plastic before it solidifies. Additionally, plastisol and organosol casting processes involve melting the polymer in a plasticizer matrix and then forming a film through the solvent action of the plasticizer.
[0006] In conventional methods and apparatus, the solution containing the base polymer and secondary components such as plasticizers, fillers, surfactants, activators, and colorants, which is ultimately cast onto a moving surface, is prepared by combining the base polymer and secondary components with water in a tank and then mixing. The homogenous solution or suspension is then pumped through one or more operations, including degassing and filtering, and then fed to a solution casting die for casting onto a moving surface, such as a moving belt.
[0007] Recently, methods have been developed for continuously producing solvent cast films using a pressurized stream of PvOH solution, combining with a stream of fluid containing a crosslinker, in-line mixing the combined PvOH solution and crosslinker stream, continuously applying the resulting homogenous mixture of PvOH solution and crosslinker to a moving surface, and then evaporating the solvent from the mixture (see, for example, U.S. Patent Application Publication No. 2007 / 0085235, the entire contents of which are incorporated herein by reference). However, such methods require the use of complex machinery and multiple solvents.
[0008] Thus, it would be desirable to devise a method that uses simpler process steps / equipment to obtain a film with the desired barrier coating properties. Summary of the Invention
[0009] The present disclosure relates to methods of making films that involve modifying polymer films using a printed crosslinker such that the resulting crosslinked polymer is less soluble compared to a crosslinked polymer made by combining the crosslinker and polymer in solution. Articles of manufacture produced by such methods are also disclosed.
[0010] In one embodiment, a method of making a crosslinked film is disclosed that includes applying a polymer solution to a substrate, drying the polymer solution on the substrate, printing a crosslinker onto the dried substrate, and heating the printed substrate for a sufficient time to achieve crosslinking, where the resulting crosslinked polymer exhibits greater insolubility compared to a crosslinked polymer produced by application of the same polymer and crosslinker combined in solution. In a related aspect, the method optionally further includes evaporating an optional solvent from the heated substrate to form a crosslinked polymer film.
[0011] In one embodiment, the polymer includes polyvinyl alcohol, polyethylene oxide, dextran, starch, cellulose derivatives (e.g., hemicellulose, hydroxyethyl cellulose, hydroxypropyl cellulose and other cellulose ethers), lignin, polyvinylpyrrolidone, polyacrylamide, polyacrylic acid, polyacrylates, pectin, alginates, proteins, derivatized proteins (e.g., gelatin, corn zein, whey protein), and combinations thereof. In a related embodiment, the polymer is polyvinyl alcohol.
[0012] In another embodiment, the substrate is a cellulosic material.
[0013] In one embodiment, the crosslinking agents include aldehydes, aldehyde-containing resins, multifunctional carboxylic acids, difunctional methacrylates, N-lactam carboxylates, dithiols, dimethylurea, diisocyanates, borates, salts of polyvalent anions, inorganic polyions, Group 1B salts, polyamide-epichlorohydrin resins, and combinations thereof.
[0014] In a related aspect, the crosslinking agent includes an aldehyde, an aldehyde-containing resin, a dicarboxylic acid, and combinations thereof. In a related aspect, the crosslinking agent includes an aldehyde. In a related aspect, the crosslinking agent includes a dialdehyde. In another related aspect, the crosslinking agent includes glyoxal, glutaraldehyde, or a mixture thereof. In a further related aspect, the crosslinking agent is glyoxal.
[0015] In one embodiment, the crosslinker is present in an amount up to about 10% by weight based on the weight of the polymer, hi another embodiment, the polymer is present in an amount ranging from about 50% to 90% by weight based on the weight of the polymer solution.
[0016] In another embodiment, printing includes flexography, gravure, inkjet, indigo, and offset printing.
[0017] In one embodiment, the cellulosic materials include paper, paperboard, paper pulp, food storage cartons, food storage bags, shipping bags, coffee or tea containers, tea bags, bacon board, diapers, weed inhibition / barrier fabrics or films, weed control films, flower pots, packing beads, bubble wrap, oil absorbing materials, laminates, envelopes, gift cards, credit cards, gloves, raincoats, greaseproof paper, shopping bags, compost bags, release paper, tableware, containers for holding hot or cold beverages, cups, paper towels, dishes, bottles for storing carbonated liquids, insulating materials, carbonated These include empty liquid storage bottles, food wrap films, food waste disposal containers, food handling utensils, cup lids, paper straws, fabric fibers, water storage and transport devices, paperboard for medical applications, release papers, alcoholic or non-alcoholic beverage storage and transport devices, exterior casings or screens for electronic products, interior or exterior components of furniture, curtains, upholstery, films, boxes, sheets, trays, pipes, water conduits, packaging for pharmaceutical products, clothing, medical devices, contraceptives, camping equipment, molded cellulosic materials, and combinations thereof.
[0018] In one embodiment, the method controllably derivatizes a substrate for hydrophobic and / or oleophobic resistance. In a related embodiment, the resulting substrate is hydrophobic. In a related embodiment, the resulting substrate is oleophobic. In another related embodiment, the resulting substrate exhibits a 3M Grease KIT test value between 3 and 12.
[0019] In one embodiment, the polymer solution is provided as an emulsion.
[0020] In another embodiment, the polymer solution comprises one or more of clay, carbonate, calcium carbonate, titanium dioxide, plastic pigment, binder, starch, protein, polymer emulsion, latex, zirconium salt, calcium stearate, lecithin oleate, polyethylene emulsion, carboxymethyl cellulose, acrylic polymer, alginate, polyacrylate rubber, polyacrylate, microbicide, oil-based defoamer, silicone-based defoamer, stilbene, direct dye, or acid dye.
[0021] In one embodiment, an article of manufacture is disclosed that includes a substrate having a crosslinked polymeric coating layer, where the crosslinks are substantially confined to a top surface of the layer and are substantially free of crosslinks within the layer.
[0022] In a related aspect, the crosslinked polymer layer provides an article of manufacture with greater flexibility, less stiffness, and / or greater elongation compared to an article of manufacture that includes a substantially similar crosslinker and polymer but in which substantial crosslinks are contained within the layer. [Brief description of the drawings]
[0023] [Figure 1] Diagrams of two reactions are shown where crosslinking of the polymer occurs on and within the film when the crosslinking reaction is carried out in solution (top-part reaction, prior art) or where crosslinking occurs on the exposed surface of the cured / dried polymer when a crosslinker is printed onto said surface (bottom-part reaction). Noteworthy is the qualitative difference in crosslink density between the products of the two reactions. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0024] Before describing the present compositions, methods, and methodologies, it should be understood that the invention is not limited to the particular compositions, methods, and experimental conditions described, as such may vary. It should also be understood that the scope of the invention is limited by the appended claims, and that the terminology used herein is for the purpose of describing particular embodiments only, and is not intended to be limiting.
[0025] As used in this specification and the appended claims, the singular forms "a," "an," and "the" include plural references unless the context clearly dictates otherwise. For example, reference to a "polymer" includes one or more polymers and / or compositions of the type described herein that will be apparent to one of ordinary skill in the art upon reading this disclosure, etc.
[0026] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this invention belongs. It is understood that modifications and variations are encompassed within the spirit and scope of this disclosure, and therefore any methods and materials similar or equivalent to those described herein can be used in the practice or testing of the present invention.
[0027] As used herein, the terms "about," "approximately," "substantially," and "significantly" are understood by those of ordinary skill in the art and will vary to some extent depending on the context in which they are used. If there are uses of a term that are not clear to a person of ordinary skill in the art given the context in which the term is used, "about" and "approximately" mean plus or minus <10% of the particular term, and "substantially" and "significantly" mean plus or minus >10% of the particular term. "Comprising" and "consisting essentially of" have their accustomed meanings in the art.
[0028] Previous methods and systems for producing crosslinked films, particularly crosslinked PvOH, have been performed by combining the crosslinker and polymer in solution (Figure 1, top reaction). In contrast, the methods described herein involve printing one or more crosslinkers onto a previously applied base polymer to form the final film (Figure 1, bottom reaction). Among the advantages that can be gained by various embodiments of the method are the adaptability and efficiency of the method in producing more insoluble films by more effectively reaching the -OH groups on the film surface.
[0029] As described herein, the crosslinking agent is applied onto the polymer film surface by printing or using the crosslinking agent in a manner similar to an overcoat varnish. Without being bound by any theory, after the polymer film is set / dried, the crosslinking agent is printed onto the dried / cured surface and most likely reacts with the most available -OH groups on the surface. Application and rapid heating (e.g., less than 1 minute) after application can cause a reaction to occur on the surface to form a crosslinked network that insolubilizes the surface while aiding gloss.
[0030] Benefits include, but are not limited to, ag film applications where lower solubility ensures slower material degradation in situ, including overall savings that may be realized due to lower PvOH content required to achieve the intended functionality. In a parallel vein, the disclosed method may be useful in products where an insoluble PvOH outer layer is desired (e.g., providing improved tactility and appearance in paper straws).
[0031] By optimizing the amount of polymer and crosslinker, the number of products containing such films can be increased. The disclosed method shows a clear difference from mixing polymer and crosslinker in solution. When such a mixture is applied to paper and then dried at a high enough temperature to ensure crosslinking, the film becomes much more soluble when immersed in water compared to products produced by the disclosed method. Without being bound by theory, due to the resulting structural difference (see FIG. 1) due to the idea that substantial crosslinking should not occur throughout the thickness of the film, the mechanical properties of the film from the disclosed method are different, including but not limited to exhibiting higher flexibility, lower stiffness, and higher elongation.
[0032] As used herein, "aqueous" usually means of or containing water as the solvent or medium.
[0033] As used herein, "biobased" refers to a material that is intentionally made from substances derived from living (or formerly living) organisms. In a related aspect, a material that contains at least about 50% of such substances is considered to be biobased.
[0034] As used herein, "bind," including grammatical variations thereof, means to adhere or cause to adhere essentially as a single unit.
[0035] As used herein, "cellulosic" refers to natural, synthetic, or semi-synthetic materials that can be molded or extruded into objects (e.g., bags, sheets) or films or filaments and can be used to make such objects or films or filaments, and that are structurally and functionally similar to cellulose, e.g., coatings and adhesives (e.g., carboxymethylcellulose). Another example is cellulose, a complex carbohydrate composed of glucose units (CH), which forms the main component of cell walls in most plants. 10 O5) nThe cellulose is cellulosic.
[0036] As used herein, "coating weight" is the weight of material (wet or dry) applied to a substrate. Coating weights are expressed in pounds per ream or grams per square meter as specified.
[0037] As used herein, "Cobb value" refers to the water absorption rate (weight of water per unit area) of a sample. The procedure for determining "Cobb value" is performed in accordance with TAPPI Standard 441-om. Cobb value is calculated by subtracting the initial weight of the sample from the final weight of the sample, then dividing by the area of the sample covered by water. The reported value represents grams of water absorbed per square meter of paper.
[0038] As used herein, "compostable" means that the solid product is biodegradable in soil.
[0039] As used herein, "crosslinking," including grammatical variations thereof, refers to a bond that links one polymer chain to another. Such linkages can be in the form of covalent or ionic bonds, and the polymers can be either synthetic or natural polymers (such as proteins). Crosslinking agents form such linkages and include, but are not limited to, aldehydes, aldehyde-containing resins, multifunctional carboxylic acids, difunctional methacrylates, N-lactam carboxylates, dithiols, dimethylurea, diisocyanates, borates, salts of polyvalent anions, inorganic polyions, salts of Group 1B, polyamide-epichlorohydrin resins, and combinations thereof. In one embodiment, the crosslinking agent can be present in an amount of up to about 10% by weight, e.g., from about 1% to about 10% by weight, or from 5% to about 10% by weight, based on the weight of the water-soluble polymer.
[0040] As used herein, "crosslink density" refers to the number of chemical crosslinks per unit volume in a polymer. When crosslink density is defined as the reciprocal of the molecular weight between crosslinks (Mc), the crosslink density can be calculated by the following formula: Ge=pRT / Mc
[0041] where Ge is the equilibrium modulus as determined by dynamic mechanical analysis temperature sweep, p is the density (which may be determined by Archimedes method), R is the universal gas constant in J / mol*K, and T is the absolute temperature in Kelvin. Once Ge and p are found experimentally, one can calculate Mc and ultimately the crosslink density. In a related aspect, films obtained by the methods described herein may have a lower crosslink density as compared to films obtained with crosslinkers and polymers in solution.
[0042] In one embodiment, a method of making a crosslinked film is disclosed, comprising applying a polymer solution to a substrate, drying said polymer solution on the substrate, printing a crosslinker onto the dried substrate, and heating the printed substrate for a sufficient time to achieve crosslinking, wherein the resulting crosslinked polymer exhibits greater insolubility compared to a crosslinked polymer produced by application of the same polymer and crosslinker combined in solution. In a related aspect, the method optionally further comprises evaporating an optional solvent from the heated substrate to form a crosslinked polymer film.
[0043] In a related embodiment, one or more polymers may be blended prior to deposition onto a substrate, including where the one or more polymers may be different, where different polymers are crosslinked together. In another embodiment, the polymer is linked to a smaller molecule, which is added for functionality (e.g., as a crosslinker to attach low substituted sucrose esters to a substrate for water and / or grease resistance).
[0044] In one embodiment, an article of manufacture is disclosed that includes a substrate having a crosslinked polymer coating layer, the crosslinking being substantially confined to the top surface of the layer and substantially free of crosslinks within the layer. In one aspect, the article of manufacture exhibits a lower crosslink density compared to an article of manufacture produced by a process in which a mixture of a crosslinker and a polymer is deposited as a solution onto the substrate.
[0045] In one embodiment, the crosslinked polymer layer provides an article of manufacture with greater flexibility, less stiffness, and / or greater elongation compared to an article of manufacture that includes a substantially similar crosslinker and polymer but in which substantial crosslinks are contained within the layer.
[0046] In one embodiment, "edge wicking" as used herein refers to the absorption of water into a paper structure at the outer edge thereof by one or more mechanisms, including but not limited to capillary penetration of pores between fibers, diffusion through fibers and bonds, and surface diffusion on fibers. In a related aspect, the polymeric films described herein prevent edge wicking of treated products. In one aspect, a similar problem exists where grease / oil gets trapped in creases that may be present in paper or paper products. Such a "grease creasing effect" can be defined as the absorption of grease in the paper structure created by folding, pressing, or squashing the paper structure.
[0047] As used herein, "effect," including grammatical variations thereof, means imparting a particular property to a specific material.
[0048] As used herein, "hydrophobic material" refers to a material that does not attract water, for example, hydrophobic materials include waxes, rosins, resins, sugar fatty acid esters, diketene, shellac, vinyl acetate, PLA, PEI, oils, fats, lipids, other water repellent chemicals, or combinations thereof.
[0049] As used herein, "hydrophobic" refers to the property of being water repellent and tending to repel and not absorb water.
[0050] As used herein, "lipid resistance" or "oleophobicity" refers to the property of being lipid repellent and tending to repel and not absorb lipids, grease, fats, etc. In a related aspect, grease resistance can be measured by the "3M KIT" test or the TAPPI T559 Kit test.
[0051] As used herein, "laminate structure" means an article of manufacture constructed from multiple layers of sheet material bonded together by an adhesive. For example, paper tubes, drinking straws, and corrugated cardboard are all laminate structures.
[0052] As used herein, "cellulose-containing material" or "cellulose-based material" refers to a composition that is essentially composed of cellulose. For example, such materials may include, but are not limited to, paper, paper sheets, paperboard, paper pulp, food storage cartons, parchment paper, cake board, butcher paper, release paper / liner, paper straws, food storage bags, drinking paper straws, paper tubes, corrugated cardboard, shopping bags, shipping bags, bacon board, insulation materials, tea bags, coffee or tea containers, compost bags, tableware, containers for holding hot or cold beverages, cups, lids, dishes, carbonated liquid storage bottles, gift cards, non-carbonated liquid storage bottles, food wrap films, food waste disposal containers, food handling equipment, fabric fibers (e.g., cotton or cotton blends), water storage and transport equipment, alcoholic or non-alcoholic beverages, external casings or screens for electronic products, interior or exterior components of furniture, curtains, and upholstery products.
[0053] "Release paper" as used herein means a paper sheet used to prevent tacky surfaces from prematurely adhering to adhesives or mastics. In one aspect, the films described herein can be used to produce materials with low surface energy, replacing or reducing the use of silicon or other coatings. Surface energy can be easily determined by measuring contact angles (e.g., Optical Tensiometer and / or High Pressure Chamber; Dyne Testing, Staffordshire, United Kingdom) or by using Surface Energy Test Pens or Inks (see, e.g., Dyne Testing, Staffordshire, United Kingdom).
[0054] As used herein, "substrate" means a material that provides a surface upon which something may be deposited or inscribed.
[0055] As used herein, "fiber in solution" or "pulp" refers to a lignocellulosic fibrous material prepared by chemically or mechanically separating cellulose fibers from wood, fiber crops, or waste paper. In related aspects where the cellulose fibers are treated by the methods described herein, the cellulose fibers themselves contain the films that bind them as isolated entities, and the bound cellulose fibers have properties that are separate and distinct from the free fibers.
[0056] As used herein, "repulpable" means rendering the paper or paperboard product suitable for being crushed into a shapeless, flexible mass for reuse in the manufacture of paper or paperboard.
[0057] As used herein, "adjustable," including grammatical variations thereof, means adjusting or adapting a process to achieve a particular result.
[0058] As used herein, "water contact angle" means the angle, measured through a liquid, where a liquid / vapor interface meets a solid surface. The water contact angle quantifies the wettability of a solid surface by a liquid. The contact angle reflects how strongly liquid and solid molecules interact with each other compared to how strongly each interacts with its own kind. On many highly hydrophilic surfaces, a drop of water exhibits a contact angle of 0°-30°. In general, a solid surface is considered hydrophobic if the water contact angle is greater than 90°. Water contact angles can be readily obtained using an optical tensiometer (see, e.g., Dyne Testing, Staffordshire, United Kingdom).
[0059] "Water vapour permeability" here means breathability, or the ability of a textile to transport moisture. There are at least two different methods of measurement. One of them, the MVTR (Water Vapour Transmission Rate) test according to ISO 15496, describes the water vapour permeability (WVP) of a fabric, i.e. the degree of sweat transport to the outside air. The measurement determines how many grams of moisture (water vapour) pass through one square meter of fabric in 24 hours (the higher the level, the more breathable it is).
[0060] In one embodiment, the TAPPI T 530 Hercules size test (i.e., paper sizing test by ink fastness) may be used to determine water fastness. Ink fastness by the Hercules method is best classified as a test for direct measurement of penetration. It may also be classified as a penetration rate test. There is no one test that is best for "measuring sizing." Test selection depends on the end use and mill control needs. Such a method is particularly suited for use as a mill control sizing test that accurately detects changes in sizing levels. This method offers the sensitivity of the ink float test while providing reproducible results, shorter test times, and automatic end point determination.
[0061] Sizing, measured by the resistance of aqueous liquids to penetration or absorption through the paper, is an important characteristic of many papers, typical of which are bag, container board, meat wrap, writing, and some printing grades.
[0062] Such methods may be used to monitor the production of paper or paperboard for a particular end use, provided an acceptable correlation is established between the test values and the end-use performance of the paper. Due to the nature of the test and the permeants, they may not correlate sufficiently to be applicable to all end-use requirements. This method measures sizing by penetration rate. Other methods measure sizing by surface contact, surface penetration, or absorption. Sizing tests are selected based on their ability to simulate the means of water contact or absorption in the end use. Such methods can also be used to optimize size chemical usage costs.
[0063] Tests performed may also include, but are not limited to, bond strength, set time, smoothness, paper stiffness, water resistance (hot and cold), printability, beam strength, ease of cutting, molding, and putty adhesion.
[0064] As used herein, "oxygen permeability" refers to the degree to which a polymer allows the passage of a gas or fluid. The oxygen permeability (Dk) of a material is a function of its diffusivity (D) (i.e., the rate at which oxygen molecules traverse the material) and its solubility (k) (or the amount of oxygen molecules absorbed per volume of the material). Oxygen permeability (Dk) values are typically in the range of 10 to 150 x 10 -11 (cm 2ml O2 / (s ml mmHg). A semi-logarithmic relationship has been demonstrated between hydrogel water content and oxygen permeability (units: Barrer). The International Organization for Standardization (ISO) defines permeability using the SI unit of pressure, hectopascals (hPa). Thus, Dk = 10 -11 (cm 2 ml O2) / (s ml hPa). Barrer units can be converted to hPa by multiplying them by the constant 0.75.
[0065] "Printing," as used herein, including grammatical variations thereof, means to imprint something into or on a substrate. In a related aspect, the methods described herein may include aqueous printing techniques, including, but not limited to, flexographic printing, UV printing, gravure printing, inkjet printing, indigo printing, and offset printing.
[0066] As used herein, "polymer" refers to a substance having a molecular structure that is composed primarily or entirely of a number of similar units linked together. For example, such polymers include, but are not limited to, polyvinyl alcohol, polyethylene oxide, dextran, starch, cellulose derivatives (e.g., hemicellulose, hydroxyethyl cellulose, hydroxypropyl cellulose and other cellulose ethers), lignin, polyvinylpyrrolidone, polyacrylamide, polyacrylic acid, polyacrylates, pectins, alginates, proteins, derivatized proteins (e.g., gelatin, corn zein, whey protein), and combinations thereof. In a related embodiment, the polymer is polyvinyl alcohol.
[0067] As used herein, "biodegradable," including grammatical variations thereof, means capable of being broken down by the action of living organisms (eg, by microorganisms), especially into harmless products.
[0068] As used herein, "recyclable," including grammatical variations thereof, means that a material can be treated or processed (with post-consumer and / or waste materials) to make the material suitable for reuse.
[0069] As used herein, "latex" refers to a stable dispersion (emulsion) of polymeric particles in an aqueous medium. Latex is found in nature, but synthetic latex can be made by polymerizing monomers such as styrene that have been emulsified with surfactants. Naturally occurring latex is a milky fluid found in 10% of all flowering plants (angiosperms). Latex is a complex emulsion of proteins, alkaloids, starches, sugars, oils, tannins, resins, and gums that coagulates when exposed to air.
[0070] "Filler" herein means finely divided white minerals (or pigments) added to papermaking furnishes to improve the optical and physical properties of the sheet. The particles serve to fill the spaces and interstices between the fibers, thereby producing a sheet with increased brightness, opacity, smoothness, gloss, and printability, but usually with reduced bond and tear strength. Common papermaking fillers include clays (kaolin, bentonite), calcium carbonate (both GCC and PCC), talc (magnesium silicate), and titanium dioxide.
[0071] As used herein, "Gurley second" or "Gurley number" is a unit of measurement that describes the number of seconds required for 100 cubic centimeters (deciliters) of air to pass through 1.0 square inch of a given material at a pressure differential of 4.88 inches of water (0.176 psi) (ISO 5636-5:2003) (porosity). Also, for stiffness, "Gurley number" is a unit of measurement that measures the force (1 milligram force) required to deflect a piece of material held vertically a given amount. Such values can be measured with Gurley Precision Instruments (Troy, New York).
[0072] As used herein, "wet strength" refers to a measure of how well the web of fibers holding the paper together can resist the force of breakage when the paper is wet. Wet strength can be measured using a Finch Wet Strength Device from Thwing-Albert Instrument Company (West Berlin, NJ). In such cases, wet strength is typically provided by wet strength additives such as polyamidoamine-epichlorohydrin resins, polyamine-epichlorohydrin resins, including kymenes, cationic glyoxylated resins, and epoxide resins. In one embodiment, the films described herein provide such wet strength in the absence of such additives.
[0073] As used herein, "wet" means covered or saturated with water or another liquid.
[0074] As described herein, the printing method has demonstrated that the amount of PvOH can be reduced to produce an insoluble film. PvOH is a good film former by itself and is known in the art to form strong hydrogen bonds with cellulose, but is not very resistant to water, especially hot water. In one aspect, PvOH provides an abundant source of OH groups for crosslinking along the fibers, which increases the strength of the paper, e.g., especially wet strength, and water resistance, beyond what is possible with PvOH alone. Crosslinking agents can include dialdehydes (e.g., glyoxal, glutaraldehyde, etc.).
[0075] In one embodiment, the substrate may include starch, which may be derived from any source, such as dent corn starch, waxy corn starch, potato starch, wheat starch, rice starch, sago starch, tapioca starch, sorghum starch, sweet potato starch, and mixtures thereof.
[0076] More specifically, the starch may be unmodified starch or starch that has been modified by chemical, physical or enzymatic processes.
[0077] Chemical processing includes the optional treatment of starch with chemicals to produce modified starch (e.g., plastarch material). Included within the scope of chemical processing are, but are not limited to, starch depolymerization, starch oxidation, starch reduction, starch etherification, starch esterification, starch nitrification, starch defatting, starch hydrophobization, etc. Chemically modified starch can also be prepared by using any combination of chemical treatments. Examples of chemically modified starches include the reaction of starch with alkenylsuccinic anhydrides, especially octenylsuccinic anhydride, to produce hydrophobically esterified starches; the reaction of 2,3-epoxypropyltrimethylammonium chloride with starch to produce cationic starch; the reaction of ethylene oxide with starch to produce hydroxyethyl starch; the reaction of hypochlorite with starch to produce oxidized starch; the reaction of acid with starch to produce acid depolymerized starch; and the defatting of starch with solvents such as methanol, ethanol, propanol, methylene chloride, chloroform, carbon tetrachloride, etc. to produce defatted starch.
[0078] Physically modified starch is any starch that has been physically processed in any manner that provides physically modified starch. Within the scope of physical processing, including but not limited to heat treatment of starch in the presence of water, heat treatment of starch in the absence of water, optionally mechanically breaking down starch granules, pressure treatment of starch to melt starch granules, etc. Physically modified starch can also be prepared by using any combination of physical processing. Examples of physically modified starch include heat treatment of starch in an aqueous environment to swell the starch granules without granule breakage; heat treatment of anhydrous starch granules to cause polymer rearrangement; fragmentation of starch granules by mechanical disintegration; and pressure treatment of starch granules in an extruder to cause melting of starch granules.
[0079] Enzymatically modified starch is any starch that has been treated with enzymes in any manner to provide enzymatically modified starch. Enzymatic processing includes, but is not limited to, the reaction of alpha amylase with starch, the reaction of protease with starch, the reaction of lipase with starch, the reaction of phosphorylase with starch, the reaction of oxidase with starch, and the like. Enzymatically modified starch can be prepared by using any combination of enzymatic treatments. Examples of enzymatic processing of starch include the reaction of alpha amylase with starch to produce depolymerized starch; the reaction of alpha amylase debranching enzyme with starch to produce debranched starch; the reaction of protease enzyme with starch to produce starch with reduced protein content; the reaction of lipase enzyme with starch to produce starch with reduced lipid content; the reaction of phosphorylase enzyme with starch to produce enzymatically modified phosphorylated starch; and the reaction of oxidase enzyme with starch to produce enzymatically oxidized starch.
[0080] In one embodiment, the polymer solution can contain between about 10% and about 90%, about 10% and about 20%, about 30% and about 40%, about 50% and about 60%, about 70% and about 80%, or about 80% and about 90% polymer (w / w) by weight of the solution. In a related aspect, the coating can contain between about 80% and about 99% polymer (w / w) by weight of the coating.
[0081] In one embodiment, the crosslinking agent is present in an amount up to about 10% by weight based on the weight of the polymer. In a related aspect, the crosslinking agent is present in an amount ranging from about 1% to about 2%, from about 2% to about 3%, from about 3% to about 4%, from about 4% to about 5%, from about 5% to about 6%, from about 6% to about 7%, from about 7% to about 8%, from about 8% to about 9%, or from about 9% to about 10% by weight based on the weight of the polymer.
[0082] In one embodiment, the cellulose-based materials include, but are not limited to, paper, paperboard, paper sheets, paper pulp, cups, boxes, trays, lids, release paper / liners, compost bags, shopping bags, shipping bags, paper straws, paper tubes, corrugated cardboard, bacon board, tea bags, insulation materials, coffee or tea containers, pipes and conduits, disposable food cutlery, plates and bottles, screens for TVs and mobile devices, clothing (e.g., cotton or cotton blends), bandages, pressure sensitive labels, pressure sensitive tapes, feminine products, and medical devices used on or within the body, such as contraceptives, drug delivery devices, containers of pharmaceutical materials (e.g., pills, tablets, suppositories, gels, etc.), etc. The disclosed coating technology can also be used on furniture and upholstery, outdoor camping equipment, etc.
[0083] In one aspect, the coatings described herein are resistant to a pH ranging between about 3 and about 9. In related aspects, the pH can be from about 3 to about 4, from about 4 to about 5, from about 5 to about 7, or from about 7 to about 9.
[0084] In one embodiment, the polymer solution can contain adhesives, proteins, polysaccharides and / or lipids (including but not limited to milk proteins, (e.g., casein, whey protein, etc.)), wheat gluten, gelatin, prolamines (e.g., corn zein), proteins, protein isolates, starches, acetylated polysaccharides, alginates, latex, carrageenans, chitosan, inulin, long chain fatty acids, waxes, and combinations thereof.
[0085] In one embodiment, the polymer solutions described herein can be used to carry other chemicals used in papermaking, including, but not limited to, agarite, esters, diesters, ethers, ketones, amides, nitriles, aromatics (e.g., xylene, toluene), acid halides, anhydrides, alkyl ketene dimers (AKD), alabaster, alganic acid, alum, alvanin, glue, barium carbonate, barium sulfate, chlorine dioxide, dolomite, diethylenetriamine pentaacetate, EDTA, enzymes, formamidine sulfate, guar gum, gypsum, lime, magnesium bisulfate, milk of lime, milk of magnesia, rosin, rosin soap, satin, soap / fatty acids, sodium bisulfate, soda ash, titania, surfactants, starch, modified starch, hydrocarbon resins, polymers, waxes, polysaccharides, proteins, latex, and combinations thereof. In one embodiment, the disclosed polymer solutions can contain one or more polymers and one or more of the following inorganic particles: clay (kaolin, bentonite), calcium carbonate (both GCC and PCC), talc (magnesium silicate), and titanium dioxide.
[0086] In one embodiment, the films produced by the methods described herein exhibit greater insolubility compared to films not produced by the disclosed methods. In a related aspect, the resulting films may exhibit greater oleophobicity or grease resistance compared to films produced by solutions containing a combination of crosslinker and polymer. In a further related aspect, the resulting films may be biodegradable, compostable, and / or recyclable. In one aspect, the resulting films are hydrophobic (water resistant) and / or oleophobic (grease resistant).
[0087] In one embodiment, the film obtained as described herein may have improved mechanical properties compared to films not made by this method. For example, paper bags treated by the process described herein may exhibit increased burst strength, Gurley number, tensile strength and / or energy at maximum load. In one aspect, the burst strength is increased by a factor of between about 0.5-1.0, between about 1.0-1.1, between about 1.1-1.3, and between about 1.3-1.5. In another aspect, the Gurley number is increased by a factor of between about 3-4, between about 4-5, between about 5-6, and between about 6-7. In yet another aspect, the tensile strain is increased by a factor of between about 0.5-1.0, between about 1.0-1.1, between about 1.1-1.2, and between about 1.2-1.3. In yet another embodiment, the energy at peak load is increased by a factor of between about 1.0-1.1 times, between about 1.1-1.2 times, between about 1.2-1.3 times, and between about 1.3-1.4 times.
[0088] In one embodiment, the cellulose-containing material is a base paper comprising microfibrillated cellulose (MFC) or cellulose nanofibers (CNF), e.g., as described in U.S. Patent Application Publication No. 2015 / 0167243, incorporated herein by reference in its entirety, and MFC or CNF is added during the forming and papermaking process and / or added to a previously formed layer as a coating or secondary layer to reduce the porosity of the base paper. In a related aspect, the base paper is contacted with a polymer solution and printed as described above. In a further related aspect, the polymer in the contacted base paper is PvOH. In one embodiment, the resulting contacted base paper is controllably water- and grease-resistant. In a related aspect, the resulting base paper may exhibit a Gurley value of at least about 10-15 (i.e., Gurley Air Flow (sec / 100cc, 20 oz. cylinder)), or at least about 100, at least about 200 to about 350. In one aspect, the film can act as a laminate of one or more layers or can comprise one or more layers as a laminate or the amount of coating of one or more layers can be reduced to obtain the same performance effect (e.g., water resistance, grease resistance, etc.) In a related aspect, the laminate can include a heat seal or adhesive that is biodegradable and / or compostable.
[0089] In one embodiment, the polymer solution may be formulated as an emulsion, and the choice of emulsifier and the amount used is determined by the nature of the composition and the ability of the emulsifier to promote dispersion of the polymer. In one aspect, the emulsifier may include, but is not limited to, water, buffers, carboxymethylcellulose (CMC), latex, milk protein, wheat gluten, gelatin, prolamin, soy protein isolate, starch, acetylated polysaccharides, alginates, carrageenans, chitosan, inulin, long chain fatty acids, fatty acid esters, sucrose esters, waxes, agar, alginates, glycerol, gums, lecithin, poloxamer, monoglycerol, diglycerol, monosodium phosphate, monostearate, propylene glycol, detergents, cetyl alcohol, and combinations thereof. In other embodiments, the ratio of polymer:emulsifier can be about 0.1:99.9, about 1:99, about 10:90, about 20:80, about 35:65, about 40:60, and about 50:50, although it will be apparent to one of skill in the art that the ratio may vary depending on the desired properties of the final product.
[0090] In one embodiment, the polymer may be combined with one or more coating components (single or in combination) for interior and surface sizing, including, but not limited to, binders (e.g., starches, proteins, latexes, polymer emulsions), additives (e.g., zirconium salts, calcium stearate, lecithin oleate, polyethylene emulsions, carboxymethylcellulose, acrylic polymers, alginates, polyacrylate rubbers, polyacrylates, microbicides, oil-based defoamers, silicone-based defoamers, stilbenes, direct and acid dyes), and varnishes. In a related aspect, such components may provide one or more properties including, but not limited to, building a microporous structure, providing a light scattering surface, improving ink acceptance, improving gloss, binding pigment particles, binding the coating to paper, base sheet reinforcement, filling pores in the pigment structure, reducing water sensitivity, resisting wet pick in offset printing, preventing blade scratching, improving gloss in supercalendering, reducing dusting, adjusting coating viscosity, achieving water retention, dispersing pigments, maintaining coating dispersion, preventing coating / coating colorant degradation, controlling foaming, reducing entrained air and coating craters, increasing whiteness and brightness, and controlling color and shade. However, it will be apparent to one skilled in the art that combinations may be varied depending on the properties desired in the final product.
[0091] The disclosed methods may be used to lower the cost of applying primary / secondary coatings (e.g., silicone-based layers, starch-based layers, clay-based layers, PLA layers, Bio-PBS, PEI layers, etc.) by providing a layer of material that exhibits a desired property (e.g., water resistance, low surface energy, etc.), thereby reducing the amount of primary / secondary layer required to obtain the same property. In one embodiment, the composition is fluorocarbon- and silicone-free.
[0092] In one embodiment, the composition enhances both the mechanical and thermal stability of the treated product. In one aspect, the surface treatment is thermally stable at temperatures between about -100°C and about 300°C. In a further related aspect, the surface of the cellulose-based material exhibits a water contact angle between about 60° and about 120°. In another related aspect, the surface treatment is chemically stable at temperatures between about 200°C and about 300°C.
[0093] The substrate, which is dried (e.g., at about 80-150°C) before application, can be treated with the crosslinking agent by printing. The substrate can be heated to dry the surface, after which the modified material is ready for use. In one embodiment, the substrate can be treated with an optional suitable coating / sizing process, typically performed in a paper mill, according to the methods described herein (see, for example, Smook, G., Surface Treatments, Handbook for Pulp & Paper Technologists, (2016), 4th Ed., Cpt. 18, pp. 293-309, TAPPI Press, Peachtree Corners, GA USA, which is incorporated herein by reference in its entirety).
[0094] In one embodiment, the disclosed method can be used on any cellulose-based surface, including but not limited to films, rigid containers, fibers, pulp, fabrics, and the like.
[0095] Depending on the source, the cellulose can be paper, paperboard, pulp, softwood fibers, hardwood fibers, or combinations thereof, nanocellulose, cellulose nanofibers, whiskers or microfibrils, microfibrillated cotton or cotton blends, other non-wood fibers (such as sisal, jute or hemp, flax and straw), cellulose nanocrystals, or nanofibrillated cellulose.
[0096] In one embodiment, the amount of polymer solution applied is sufficient to completely cover at least one surface of the cellulose-containing material. For example, in one embodiment, the polymer solution may be applied to the entire outer surface of the container, the entire inner surface of the container, or a combination thereof, or to one or both sides of the base paper. In other embodiments, the entire upper surface of the substrate may be covered by the polymer solution, or the entire lower surface of the substrate may be covered by the polymer solution, or a combination thereof. In some embodiments, the lumen of the device / instrument may be covered by the polymer solution, or the outer surface of the device / instrument may be covered by the polymer solution, or a combination thereof. In one embodiment, the amount of polymer solution applied is sufficient to partially cover at least one surface of the cellulose-containing material. For example, only the surface exposed to the ambient atmosphere is covered by the polymer solution, or only the surface not exposed to the ambient atmosphere is covered by the polymer solution (e.g., masked). As will be apparent to one skilled in the art, the amount of polymer solution applied may depend on the use of the material to be coated. In one aspect, one surface may be coated with a polymer solution and the opposing surface may be coated with an agent including, but not limited to, proteins, wheat gluten, gelatin, prolamins, protein isolates, starches, modified starches, acetylated polysaccharides, alginates, carrageenans, chitosan, inulin, long chain fatty acids, waxes, and combinations thereof. In a related aspect, the polymer solution may be added to the furnish and the resulting material on the web may be provided with an additional coating of the polymer solution.
[0097] It will be apparent to one skilled in the art that the selection of treated cellulose, polymer, crosslinker, reaction temperature, and exposure time are process parameters that may be optimized by routine experimentation to suit the optional specific application of the final product.
[0098] The derivatized materials have altered physical properties that can be defined and measured using appropriate tests known in the art. For hydrophobicity, analytical protocols can include, but are not limited to, contact angle measurements and moisture uptake. Other properties include stiffness, WVTR, porosity, tensile strength, lack of substrate degradation, burst and tear properties. Specific standardized protocols to be followed are defined by the American Society for Testing and Materials (Protocol ASTM D7334-08).
[0099] The permeability of a surface to various gases, such as water vapor and oxygen, can also be modified when the disclosed process enhances the barrier function of the material. The standard unit of measurement for permeability is the barrer, and protocols for measuring these parameters are also available in the public domain (ASTM Standard F2476-05 for water vapor and ASTM Standard F2622-8 for oxygen).
[0100] In one embodiment, materials processed according to the procedures of the present disclosure exhibit complete biodegradability as measured by degradation in an environment under microbial corrosion.
[0101] Various methods are available for determining and testing biodegradability, including the shake flask method (ASTM E1279-89(2008)) and the Zahn-Wellens test (OECD TG 302 B).
[0102] A variety of methods are available for determining and testing compostability, including but not limited to ASTM D6400.
[0103] Materials suitable for treatment with the process of the present invention include various forms of cellulose, such as cotton fibers, vegetable fibers such as flax, wood fibers, regenerated cellulose (rayon and cellophane), partially alkylated cellulose (cellulose ethers), partially esterified cellulose (acetate rayon), and other modified cellulose materials, all of which have a substantial proportion of surface area available for reaction / bonding. As stated above, the term "cellulose" includes all of these materials, as well as others with similar polysaccharide structures and similar properties. Of these, the relatively new material microfibrillated cellulose (cellulose nanofibers) (see, for example, U.S. Pat. No. 4,374,702, U.S. Patent Application Publication Nos. 2015 / 0167243 and 2009 / 0221812, all of which are incorporated herein by reference) is particularly suitable for such applications. In other embodiments, the cellulose may include, but is not limited to, cellulose triacetate, cellulose propionate, cellulose acetate propionate, cellulose acetate butyrate, nitrocellulose (cellulose nitrate), cellulose sulfate, celluloid, methylcellulose, ethylcellulose, ethylmethylcellulose, hydroxyethylcellulose, hydroxypropylcellulose, cellulose nanocrystals, hydroxyethylmethylcellulose, hydroxypropylmethylcellulose, ethylhydroxyethylcellulose, carboxymethylcellulose, and combinations thereof.
[0104] In addition to increasing its hydrophobicity, the modifications of cellulose described herein may also increase its tensile strength, flexibility and stiffness, thereby further expanding its range of uses. All biodegradable and partially biodegradable products made from or by using the modified cellulose disclosed in this application are within the scope of this disclosure, including recyclable and compostable products.
[0105] Among the possible uses of the coating technology, such items include, but are not limited to, paper, paperboard, paper pulp, cups, lids, boxes, trays, release paper / liners, compost bags, shopping bags, containers for all purposes such as pipes and water lines, disposable cutlery for food, plates and bottles, screens for TVs and portable devices, clothing (e.g., cotton or cotton blends), bandages, pressure sensitive labels, pressure sensitive tapes, feminine products, and medical devices used on or within the body such as contraceptives, drug delivery devices, etc. The disclosed coating technology can also be used on furniture and upholstery, outdoor camping equipment, and the like.
[0106] The following examples are intended to illustrate, but not limit, the invention. EXAMPLES
[0107] [Example 1] Polyvinyl alcohol (PvOH) was coated onto 20# bleached hardwood sheets using a rod coater. PvOH (Selvol 425 from Sekisui Chemical, Japan) film was applied at 5 g / m 2 Glyoxal was applied to the paper by offset rotary printing (heat set). printing The films were then tested for water resistance. 5 mL of water was placed on both the untreated and glyoxal-treated PvOH films and left for 15 minutes. After 15 minutes, the untreated PvOH film was dissolved in water and the paper substrate was saturated with water. The treated paper retained an insolubilized PvOH film on its surface as evidenced by water pooling on the film.
[0108] [Example 2] The fully hydrolyzed PvOH was coated onto the first base paper to obtain a film that finally made the paper particularly water resistant. 2 The second base paper was coated at 4 g / m 2It was found that nearly similar properties could be obtained by using PvOH at a coating weight of 0.1 glyoxal and then printing with glyoxal to crosslink the surface -OH groups.
[0109] Although the invention has been described with reference to the above examples, it will be understood that modifications and variations are encompassed within the spirit and scope of the invention. The invention is limited only by the claims that follow. All references cited herein are incorporated by reference in their entirety.
Claims
1. 1. A method for making a crosslinked film, comprising the steps of: a) applying a polymer solution to a substrate; b) drying the polymer solution on the substrate; and c) printing a crosslinker onto the dried substrate; d) heating the printed substrate for a time sufficient to effect crosslinking to form a crosslinked polymer film; Including, The method wherein the resulting crosslinked polymer exhibits greater insolubility as compared to a crosslinked polymer produced by application of the same polymer and crosslinker combined in solution.
2. 2. The method of claim 1, wherein the polymer is selected from the group consisting of polyvinyl alcohol, polyethylene oxide, dextran, starch, hemicellulose, hydroxyethyl cellulose, hydroxypropyl cellulose, cellulose ethers, lignin, polyvinylpyrrolidone, polyacrylamide, polyacrylic acid, polyacrylates, pectin, alginate, protein, gelatin, corn zein, whey protein, and combinations thereof.
3. The method of claim 2 , wherein the substrate is a cellulosic material.
4. The method of claim 3 , wherein the polymer is polyvinyl alcohol.
5. 2. The method of claim 1, wherein the crosslinking agent is selected from the group consisting of aldehydes, aldehyde-containing resins, multifunctional carboxylic acids, difunctional methacrylates, ammonium zirconium carbonate, N-lactam carboxylates, dithiols, dimethylurea, diisocyanates, borates, salts of polyvalent anions, inorganic polyions, Group 1B salts, polyamide-epichlorohydrin resins, and combinations thereof.
6. The method of claim 5 , wherein the crosslinking agent is selected from the group consisting of an aldehyde, an aldehyde-containing resin, a dicarboxylic acid, and combinations thereof.
7. The method of claim 6 , wherein the cross-linking agent comprises an aldehyde.
8. The method of claim 7 , wherein the cross-linking agent comprises a dialdehyde.
9. The method of claim 8 , wherein the cross-linking agent comprises glyoxal, glutaraldehyde, or a mixture thereof.
10. The method of claim 9 , wherein the cross-linking agent is glyoxal.
11. The method of claim 1 , wherein the crosslinking agent is present in an amount of up to 10% by weight based on the weight of the polymer.
12. The method of claim 11, wherein the polymer is present in an amount ranging from 50% to 90% by weight based on the weight of the polymer solution.
13. 10. The method of claim 1, wherein said printing is selected from the group consisting of flexographic printing, gravure printing, inkjet printing, indigo printing, and offset printing.
14. The cellulosic material may be any of a variety of materials, including paper, paperboard, paper pulp, food storage cartons, food storage bags, shipping bags, coffee or tea containers, tea bags, bacon board, diapers, weed inhibition / barrier fabrics or films, weed control films, flower pots, packing beads, bubble wrap, oil absorbing materials, laminates, envelopes, gift cards, credit cards, gloves, raincoats, greaseproof paper, shopping bags, compost bags, release paper, tableware, containers for holding hot or cold beverages, cups, paper towels, dishes, bottles for storing carbonated liquids, insulating materials, bottles for storing non-carbonated liquids, and the like.
4. The method of claim 3, wherein the cellulosic material is selected from the group consisting of: plastic wrap, food wrap films, food waste disposal containers, food handling equipment, lids for cups, paper straws, fabric fibers, water storage and transport equipment, paperboard for medical applications, release paper, alcoholic or non-alcoholic beverage storage and transport equipment, exterior casings or screens for electronic products, interior or exterior components of furniture, curtains, upholstery, films, boxes, sheets, trays, pipes, water conduits, packaging for pharmaceutical products, clothing, medical devices, contraceptives, camping equipment, molded cellulosic materials, and combinations thereof.
15. The method of claim 1 , wherein the substrate is controllably derivatized for hydrophobic and / or oleophobic resistance.
16. The method of claim 15 , wherein the resulting substrate is hydrophobic.
17. The method of claim 15, wherein the resulting substrate is oleophobic.
18. 18. The method of claim 17, wherein the resulting base material exhibits a 3M Grease KIT test value between 3 and 12.
19. The method of claim 1 , wherein the polymer solution is provided as an emulsion.
20. 10. The method of claim 1, wherein the polymer solution comprises one or more of clay, calcium carbonate, titanium dioxide, plastic pigments, binders, starch, proteins, polymer emulsions, latex, zirconium salts, calcium stearate, lecithin oleate, polyethylene emulsions, carboxymethyl cellulose, acrylic polymers, alginates, polyacrylate rubbers, polyacrylates, microbicides, oil-based defoamers, silicone-based defoamers, stilbenes, direct dyes, or acid dyes.
Citation Information
Patent Citations
Printing method that forms easy-to-remove print ink layer
JP2012030369A